New material platform for superconducting transmon qubits with coherence times exceeding 0.3 milliseconds - Alexander P. M. Place (Nature Portfolio, 2021)
Quantum computers based on superconducting transmon qubits are limited by single qubit lifetimes and coherence times, which are orders of magnitude shorter than limits imposed by bulk material properties. Here, the authors fabricate two-dimensional transmon qubits with both lifetimes and coherence times longer than 0.3 milliseconds by replacing niobium with tantalum in the device.